IN VITRO AND IN VIVO WOUND HEALING ACTIVITY IN CRUDE EPIDERMAL SECRETION FROM A MARINE CATFISH ARIUS DUSSUMIERI OF MUMBAI COAST - Deo, Ashutosh D; Venkateshvaran, K.; Raghubir, Ram; Devaraj, M. (Journal of Indian Fisheries Association, 2011)
Marine organisms produce elaborate pharmaceutically use full compounds. Until recently, no pharmacologic agents that could reproducibly accelerate wound healing had been identified. In the present study an attempt is made to systematically evaluate the wound healing potential of crude epidermal secretion from the marine catfish Arius dussumieri of Mumbai waters using In vitro and in vivio models on guinea pigs. The results from the Chick Chorioallantoic  Model (CAM) studies had shown angiogenic activity as compared to control at both 40 µg and 80 µg of doses with slight to moderate neo vascularisation respectively. The surface area of healing wound after seven days had shown different degrees of contraction with different doses, 0.1% extract was found to affect the highest wound contraction with 22.5% change in wound area as compared to the control, where as 1% dose caused the least wound contraction of 2.15%. Wounds treated with 0.25% and 0.50% mucus extract, on the 8th day, had the highest level of hydroxyl proline, a marker of collagen synthesis. of 24.93 and 14.19 mg/gm tissue respectively, as against the control. The indicator of Collagen cross linking enzyme Lysyl oxidase assay exhibited an increasing trend with increase in dose. This study confirms the promising wound healing activity of crude epidermal secretion of the catfish Arius dussumieri and opens avenues for more detailed experimental and clinical pharmaceutical studies with purified extract. Keywords: Healing activity, Epidermal secretion, Arius dussumieri, Mumbai Coast.